KEBIJAKAN HUKUM PIDANA TERHADAP PEMBATASAN KEWENANGAN PENYIDIKAN TERHADAP NOTARIS (Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris) - Desi Indriani (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
The criminal law policy of the authority restriction in investigation against the notary is at the stage of policy formulation of the law provided authority Honorary Council of Notaries in the proceedings against the notary is to give consent to the investigator, prosecutor or judge to take copies Minuta Deed and / or letters attached to Minuta Deed or the Protocol Notary Notaries in storage. The legal implications for restricting the authority in the investigation of the Notary of the proceedings for the notary is not in accordance with equality of citizens before the law should not discriminate between the treatments of nationals who commit criminal acts. Additionally, Notary Honorary Council approval is also contrary to the principle of independence in the judicial process. Keywords: Policy, Restriction Authority, Notary